Financial Crisis, Economic Recovery and Banking Development in Former Soviet Union Economies - Haizhou Huang; Dalia Marin; Chenggang Xu (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper explains both the onset of the financial crisis in 1998 and the striking economic recovery afterwards in Russia and other Former Soviet Union (FSU) economies. Before the crisis banks do not lend to the real sector of the economy and firms use non-bank finance, including trade credits and barter trade, to finance production. The banking failure arises due to the coexistence of adverse selection in a lemons credit market jointly with high government borrowing. The collapse of the treasury bills market in the financial crisis of August 1998 triggers a change in banks lending behavior. A strong economic recovery follows which provides initial conditions for banking development.
Keywords: 330